Primes of the form [n^c] with square-free n - Dimitrov, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 621 Let [ · ] be the floor function. We show that if 1<c<38493334, then there exist infinitely many prime numbers of the form [n^c], where n is square-free.